Implementasi Bantuan Langsung Tunai Desa (BLTD) di Pesurungan Kota Tegal - Maulida Fitri (Sahmiyya, 2022)
The COVID-19 pandemic has caused the order of life to become disorganized. Starting fromthe aspect of health, security to the financial condition of the community. Not a few people who findit very difficult to earn income in conditions where all activities are under strict restrictions. As a formof government concern for the financially underprivileged, there are actually many kinds, such as:providing various forms of social assistance, such as the Family Hope Program (PKH), Cash SocialAssistance (BST), Village Cash Direct Assistance (BLTD), Program Worker Card, and so on.However, during the Covid-19 outbreak, the government provided financial relief for the affectedcommunity, namely the Village Cash Direct Assistance (BLTD). This study aims to find out how thegovernment's efforts in distributing Village Cash Direct Assistance funds, to find out what thebenefits are for the community, and how other policies are related to this Village Cash DirectAssistance (BLTD). The method used in this research is to apply a descriptive qualitative approachand data collection is carried out through interviews with the right sources. The results showed thatthe people who received the Village Cash Direct Assistance were helped financially, but after doingthe research it turned out that not a few people felt dependent on assistance from the government. Inaddition, for the distribution of funds that are not on target, and the funds are not used properly, thegovernment takes firm action to follow up on the situation by slowly reducing the amount of fundsreceived by the public per month. In fact, this form of government concern is appropriate, and peopleshould use these funds as well as possible.